2011
DOI: 10.1021/ac200632h
|View full text |Cite
|
Sign up to set email alerts
|

Structural Characterization of Individual Vesicles using Fluorescence Microscopy

Abstract: Extrusion of hydrated lipid suspensions is frequently employed to produce vesicles of uniform size, and the resulting vesicles are often reported to be unilamellar. We describe a method for the quantitative fluorescence image analysis of individual vesicles to obtain information on the size, lamellarity, and structure of vesicles produced by extrusion. In contrast to methods for bulk analysis, fluorescence microscopy provides information about individual vesicles, rather than averaged results, and heterogeneit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 47 publications
(85 reference statements)
0
28
0
Order By: Relevance
“…Thus, if the concentration is fixed, the volume variability implies that the number of molecules will be distributed. In principle, one should be able to correct for this effect by measuring the volume on a vesicle-by-vesicle basis (51,52). This was not done in the current experiment; nevertheless, our analysis suggests that vesicle volume variability cannot account for the whole width of the plateau level distribution.…”
Section: Product Molecules Allosterically Inhibit Individual Enzyme Mmentioning
confidence: 77%
“…Thus, if the concentration is fixed, the volume variability implies that the number of molecules will be distributed. In principle, one should be able to correct for this effect by measuring the volume on a vesicle-by-vesicle basis (51,52). This was not done in the current experiment; nevertheless, our analysis suggests that vesicle volume variability cannot account for the whole width of the plateau level distribution.…”
Section: Product Molecules Allosterically Inhibit Individual Enzyme Mmentioning
confidence: 77%
“…If each leaflet contains approximately the same surface area, fluorescence should increase linearly. Furthermore, selective external leaflet quenching of these multiply-labeled intermediates and final double bilayer product should yield a fraction of the construct total fluorescence that is inversely proportional to the number of depositions 28 . Our observations agree with linear and inverse proportionality for the layer-by-layer construction and selective external leaflet quenching experiments, respectively (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To overcome these problems with ensemble assays, it is necessary to obtain information on a large and representative number of individual vesicles, for example, by using single vesicle microscopy. Previous work along these lines showed that the size distribution of the vesicles could be determined by correlating the fluorescence intensity of a lipid marker in single vesicles with DLS data (Hatzakis et al, 2009; Malle et al, 2021; Lohr et al, 2009; Olsson et al, 2015), and that tightness and lamellarity could be assessed by bleaching of the marker (Heider et al, 2011). Other studies used step-wise photobleaching assays to determine the copy number of fluorescent proteins per vesicle (Hummert et al, 2021).…”
Section: Introductionmentioning
confidence: 99%